Mental health problems in children with chronic disease at the pediatric inpatient ward of Dr. Cipto Mangunkusumo Hospital - Wangke, Lydia; Medise, Bernie Endyarni; Wirahmadi, Angga; Sekartini, Rini; Gunardi, Hartono; Soedjatmiko, Soedjatmiko (Indonesian Pediatric Society, 2025)
Background Since the survival of a patient with chronic physical illness has improved, major concerns arise about their quality of life and functioning. Childhood and adolescence are critical periods for promoting mental health because more than half of mental health problems begin at this stage, and many of those mental health problems will persist into adult life. Objective To analyze the risk of mental health problems among children hospitalized with chronic disease. Method An analytic observational study with a cross-sectional design was conducted using secondary data of 754 children aged 4-18 years admitted to the pediatric inpatient ward of Cipto Mangunkusumo Hospital, Jakarta between June 2021 and August 2022. We collected the results of subjects’ mental health screening conducted by the Growth, Development, and Social Pediatrics Division, Department of Child Health, Cipto Mangunkusumo Hospital during the subjects’ admission. Mental health problems evaluated in this study included psychosocial dysfunction screened using the Pediatric Symptom Checklist 17 (PSC-17) and depression screened using the Children’s Depression Inventory (CDI). Results Of the 754 subjects included, 520 (69.0%) were classified as having a chronic disease. The prevalence of psychosocial dysfunction and depression in children with chronic diseases was 19.6% and 6.3%, respectively. Gender, nutritional status, and height had no significant association with psychosocial dysfunction and depression in children. Children with chronic disease were more likely to develop psychosocial dysfunction (OR 2.13; 95%CI 1.31 to 3.59; P<0.001) and depression (OR 2.57; 95%CI 1.04 to 7.62; P<0.03) compared with those who did not have chronic disease. Conclusion Children with chronic disease were more likely to develop psychosocial dysfunction and depression compared to those without a chronic disease. These results highlight the importance of mental health support in pediatric patients with chronic disease.